2005
DOI: 10.1093/rpd/nch507
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the detective quantum efficiency (DQE) of digital X-ray detectors according to the novel standard IEC 62220-1

Abstract: A mobile measurement facility which complies with IEC 62220-1 has been set up to determine the detective quantum efficiency (DQE) of digital X-ray detector systems. Exemplary measurements were performed for two similar CR detector systems, a CsI-based indirect detector and an Se-based direct detector. The standardised radiation quality RQA 5 was applied for measurement and for three of these systems RQA 9 was also applied. A pronounced dependence of DQE on radiation quality was observed for the direct detector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 8 publications
1
32
0
1
Order By: Relevance
“…Many studies [2][3][4][5][6][7][8][9][10][11][12] have reported largely standardized methods to measure the physical performance of imaging systems based on the International Electrotechnical Commission IEC 62220-1 standard. 4 These studies were based on the metric-the detective quantum efficiency (DQE)-which reflects detector efficiency when forming an image using a limited number of x-ray photons, providing an input signalto-noise ratio (SNR) at a specific exposure level.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [2][3][4][5][6][7][8][9][10][11][12] have reported largely standardized methods to measure the physical performance of imaging systems based on the International Electrotechnical Commission IEC 62220-1 standard. 4 These studies were based on the metric-the detective quantum efficiency (DQE)-which reflects detector efficiency when forming an image using a limited number of x-ray photons, providing an input signalto-noise ratio (SNR) at a specific exposure level.…”
Section: Introductionmentioning
confidence: 99%
“…Many different methods for measuring DQE have been described in the literature [19,20]. Samei et al [16] described a methodology for measuring eDQE, which estimates system performance in a clinically relevant context.…”
Section: Measurement Of Edqe and Cnr To Specify Test Techniquesmentioning
confidence: 99%
“…The quantum efficiency of the detector (detector quantum efficiency or DQE) is related to how many X-ray photons that strike the detector during the recording cycle (not during the dead time) that are actually counted (Illers et al, 2005). The efficiency of the detector depends on the detector itself (detector efficiency) and the "windows" of the detector that allow X-rays to pass through but keep air and dirt out.…”
Section: Detection Of X-rays: General Concepts and Terminologymentioning
confidence: 99%